Potential sources for lipid soluble food colorants from selected Malaysian traditional vegetables - Othman, Rashidi; Mohd Hassan, Norazian; Mohd Zaifuddin, Fatimah Azzahra (Universiti Kebangsaan Malaysia (UKM), 2015)
Colour is one important characteristic to food products as it dictates consumers’ first perception on the foods’ flavour and quality. In the current food industry, most of the colorants used were derived from synthetic sources. However, due to negative health impacts of the synthetic colorants, the urgency to find natural colorants and impose it to food products is of great importance. In this study, a group of plant pigments which are potentially introduced as natural food colorants were quantified from 24 species of local traditional vegetables (ulam), characterized as neoxanthin, violaxanthin, lutein, zeaxanthin, β- cryptoxanthin, α-carotene and β-carotene by using HPLC. It was shown that Sauropus androgynus contained the highest amount of neoxanthin, violaxanthin and β-cryptoxanthin at 142.40±3.57, 28.06±0.65 and 0.07±0.00 mg/g dry weight (DW), respectively. In contrast, highest content of lutein and α-carotene were observed in Centella asiatica at 16.53±0.97 and 2.14±0.12 mg/g DW, accordingly. Meanwhile, Piper sarmentosum contained the highest zeaxanthin level (123.45±12.3 mg/g DW) and Oenanthe javanica has the largest amount of β-carotene (3.09±0.06 mg/g DW). The extracted yellow-to-red lipid soluble pigments can be further developed into commercial food colorant to replace the synthetic colorants in the market thus improving social awareness towards natural products as well as strengthening the national economy.